Feasibility test of teaching materials for mathematics learning evaluation integrated with Al Quran - Huda, Nuril; Sujarwo, Imam (Research and Social Study Institute, 2024)
The study aims to determine the level of feasibility of integrated mathematics learning evaluation teaching materials with verses of the Koran. The type of research used is research & development (R&D) by adopting the ADDIE model, namely Analyze, Design, and Develop. Data collection techniques using validation sheets and questionnaires. The product validation involved nine validators consisting of 3 material experts, three media experts, and 3 Islamic integration experts, while the practicality test involved 15, tadris mathematics students. The Aiken formula analyzed the validity test. The results showed that the results of the material and language feasibility test were 59.25% in the high category, the results of the media feasibility test were 55.55% in the medium category, and the results of the material integration feasibility test were 75.00% in the high category, and the test results practicality of 80% with the category of practical and a little revision. This mathematics learning evaluation textbook integrated with the verses of the Koran that were developed is feasible and can be used to support the lecture process.